Graves-Basedow disease and potential risk factors - Živanović Dušica; Šipetić Sandra; Stamenković-Radak Marina; Milašin Jelena (Vojnosanitetski Pregled, 2008)
Background/Aim. Graves-Basedow disease is a common multifactorial genetic syndrome, which is determined by several genes and environmental factors. The aim of the present study was to investigate the presence of risk factors for developing Graves-Basedow disease between the groups of individuals with and without Graves-Basedow disease, and to compare the presence of risk factors between the affected individuals with or without positive family history for Graves- Basedow disease. Methods. This cross-sectional study was conducted in Ćuprija (central Serbia) during a period from December 2001 to April 2002. The case group comprised 132 individuals diagnosed with Graves-Basedow disease. The control group comprised 130 subjects without any of endocrine diseases. All participants were interviewed at the Medical Center Ćuprija using structural questionnaire. Data were collected on basic demographic characteristics, exposure to various chemical and physical agents, stress, smoking and family history of Graves-Basedow disease. In statistical analysis chi-square test was used. Results. The individuals with Graves-Basedow disease were statistically significantly older (above 50) (p = 0.020), exposed to stress (p = 0.024) and to physical agents (p = 0.031), and had significantly (p = 0.000) more relatives with Graves-Basedow disease than those without the disease. Among the affected individuals with positive family history of Graves-Basedow disease the number of women was significantly higher (p = 0.000), than the affected individuals without positive family history of Graves- Basedow disease. Conclusion. In our study, as in many other, gender, age, positive family history of Graves-Basedow disease and exposure to physical agents were identified as potential risk factors for the increased incidence of Graves- Basedow disease. Different risk factors are probably responsible for developing Graves-Basedow disease among the affected individuals with or without positive family history of Graves-Basedow disease. .